Investigation of the Unit-1 nuclear reactor of Fukushima Daiichi by cosmic muon radiography. (26th April 2020) - Fujii, Hirofumi; Hara, Kazuhiko; Hayashi, Kohei; Kakuno, Hidekazu; Kodama, Hideyo; Nagamine, Kanetada; Sato, Kotaro; Kim, Shin-Hong; Suzuki, Atsuto; Sumiyoshi, Takayuki; Takahashi, Kazuki; Takasaki, Fumihiko; et al.
Abstract: We have investigated the status of the nuclear fuel assemblies in the Unit-1 reactor of the Fukushima Daiichi nuclear power plant by cosmic muon radiography. In this study, muon tracking detectors were placed outside the reactor building. We succeeded in identifying the inner structure of the reactor complex, such as the reactor containment vessel, pressure vessel, and other structures of the reactor building, through the concrete wall of the reactor building. We found that a large number of fuel assemblies were missing in the original fuel loading zone inside the pressure vessel. The natural interpretation is that most of the nuclear fuel was melted and dropped down to the bottom of the pressure vessel or even below.